Fabrication of Antibacterial Poly(ethylene terephthalate)/Graphene Nanocomposite Fibers by In Situ Polymerization for Fruit Preservation - Jiarui Wu; Qinhan Chen; Aobin Han; Min Liu; Wenhuan Zhong; Xiaojue Shao; Yan Jiang; Jing Lin; Zhenyang Luo; Jie Yang; Gefei Li (Molecules)
A novel polyester/graphene nanocomposite fiber was produced using the in situ polymerization protocol with carboxylated graphene and melt spinning technology. The resulting nanocomposite fibers were characterized by X-ray diffraction (XRD), Raman spectroscopy, differential scanning calorimeter (DSC), and scanning electron microscope (SEM). The fibers containing 0.2 wt% graphene fraction showed an excellent dispersity of graphene nanosheets in polymeric matrix. DSC test showed that the efficient polymer-chain grafting depresses the crystallization of PET chains. This graphene-contained PET fabric exhibited attractive antibacterial properties that can be employed in fruit preservation to ensure food safety.